Influence of plasma in the vicinity of Io on brightness and angular extension of Io’s magnetic footprint - Suwicha Wannawichian (2019)
© 2019, Chiang Mai University. All rights reserved. In Jupiter’s auroral region, a spot-like emission feature, called the auroral magnetic footprint, is the result of a magnetic disturbance near the extended atmosphere of Io. The magnetic footprint is direct evidence of the interaction between the atmosphere of slow-orbiting Io and the rapidly-corotating magnetic field and magnetospheric plasma of Jupiter. The result of the magnetic disturbance is that a significant amount of current is carried from the interaction region towards Jupiter’s ionosphere. Accordingly the precipitating electrons result in the auroral emission. Far ultraviolet (FUV) images of Jupiter’s auroral region were used to study this phenomenon. In 2007, using the Advanced Camera for Surveys (ACS) instrument on the Hubble Space Telescope (HST), the observation of Io’s magnetic footprint provided the opportunity for a detailed study of the correlation between the spot’s brightness and its angular size. With a strong correlation (>0.7) between the brightness and the angular size, these two physical properties were clearly related during March and June, 2007, several weeks after major volcanic eruptions on Io were observed. These results suggest a connection between the plasma supply from Io, due to the volcanic activities on Io and the satellite’s auroral magnetic footprint morphology.